Disasters and minewater : good practice and prevention - Wood, Harvey (London IWA Publishing, 2012)
Disasters and Minewater: Good Practice and Prevention draws together all of the major minewater catastrophes that have occurred over the last half century. It examines incidents to find useful and positive information of great value that could prevent future disasters.
Introduction; Disasters and Minewater, Definitions, Occurrence, Locations, Calamities, The Main Issues, Subsidiary Issues, The Law and Regulation;. Minewater and Rebound, Minewater Characterisation, Environmental Impacts of Minewater, Minewater Rebounds; Europe; North America; China; Asia; Pacific; Russia; South America; Law and Regulation; Tailings Dams; Floods and Inundation; Changes; Potential Future Catastrophe; Minewater Treatment; Global Investment and Minewater; Water Resource; In Conclusion.
Includes bibliographical references (p. [117]-122) and index.
Keywords: Mine water; Mine accidents; Mine water -- Environmental aspects; Sewage -- Purification